Antibodies to human papillomavirus types 6, 11, 16 and 18: Vertical transmission and clearance in children up to two years of age. (April 2020) - Zahreddine, Monica; Mayrand, Marie-Hélène; Therrien, Christian; Trevisan, Andrea; Dagenais, Carole; Monnier, Patricia; Laporte, Louise; Niyibizi, Joseph; Deshaies, Catherine; Carceller, Ana Maria; Fraser, William; Brassard, Paul; et al.
Abstract: Background: There is a paucity of data on the dynamics of human papillomavirus (HPV) antibodies in children. We aimed to describe the vertical transmission and clearance of antibodies against HPV6, 11, 16 and 18 in children. Methods: We used data from pregnant women recruited into the HERITAGE cohort study between 2009 and 2012 who were positive for HPV-DNA at baseline. Dried blood spots were collected during the first trimester in pregnant participants, and at birth, 6, 12, and 24 months of age in children. The level of total immunoglobulin G (IgG) against HPV6, 11, 16 and 18 were measured using Luminex immunoassays. Spearman's coefficients were used to correlate HPV antibody levels between newborns and mothers. Panel and Kaplan-Meier graphics described antibody dynamics in the first 24 months of life. Findings: Antibodies from newborns and mothers ( n = 58 pairs) were moderately to highly correlated with coefficients of 0·81 (95% confidence intervals (CI):0·70–0·88), 0·68 (95% CI:0·5–0·80), 0·90 (95% CI:0·83–0·94) and 0·85 (95% CI:0·76–0·91) against HPV6, 11, 16 and 18, respectively. In newborns seropositive at birth, anti-HPV antibodies were cleared by 80% and 100% at 12 and 24 months, respectively. Only two children presented detectable HPV antibodies at 24 months. The first child had no detectable antibodies at birth and the second presented increasing levels after two undetected measures. Interpretation: Correlation between mother and newborn IgG antibodies against HPV suggests vertical transfer. Most children cleared anti-HPV antibodies within six to 12 months. Funding: The Canadian Institutes of Health Research (CIHR)